Semantic Modeling: Computational Models of the Concepts - Wolfengagen, V (2010 International Conference on Computational Intelligence and Security, 2010)
As known, computing allows maintenance of the constructions corresponding to the needs in comprehended models which enable the computational experiment. Computing takes the enabling of such a model which corresponds to a 'theory'. The parameters of the model are systematically changing and correspond to 'entries' for the inputs. The parameterized family of its 'behaviors' is used as the 'outputs' of the model. These -- being computed, -- behaviors are matched with the real behavior of the problem domain object under the real inputs -- prototypes of model inputs. In case of conclusion that the model satisfactory reflects the features of the real object-prototype, then the real experiment can be replaced by the computational one, which is executed using the model-image.